2008
DOI: 10.1291/hypres.31.1315
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a Risk-Stratification System for the Japanese Population Based on Blood Pressure Levels: The Ohasama Study

Abstract: The aim of the present study was to propose a risk-stratification system based on self-measurement of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…The incidence of stroke also increased with elevation of the risk levels defined by the risk stratification system recommended by the guidelines. A cohort study conducted in Japan has also demonstrated the validity of the risk stratification system of the JSH 2009 guidelines [22]. These findings support the hypothesis that the blood pressure classification and risk stratifications recommended by the JSH 2009 guidelines [3] are useful in predicting the risk of stroke among Japanese.…”
Section: Discussionsupporting
confidence: 61%
“…The incidence of stroke also increased with elevation of the risk levels defined by the risk stratification system recommended by the guidelines. A cohort study conducted in Japan has also demonstrated the validity of the risk stratification system of the JSH 2009 guidelines [22]. These findings support the hypothesis that the blood pressure classification and risk stratifications recommended by the JSH 2009 guidelines [3] are useful in predicting the risk of stroke among Japanese.…”
Section: Discussionsupporting
confidence: 61%
“…The socioeconomic and demographic characteristics of Ohasama, the selection procedure of the study populations, the HBP and CBP measurement procedures, and the data collection procedures have been described previously. [5][6][7] The present study population consisted of 2369 individuals (40% men), Ն35 years of age (mean, 59.2 years), without a history of stroke and with Ն3 days of morning HBP and a CBP. 6 The subjects were followed from the dates of HBP measurement (approximately 1992) until December 31, 2004.…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for diagnosing stroke were described previously. 7,8 Cerebral infarction (International Classification of Diseases, 10th Revision code I63) was defined as ischemic stroke, and intracerebral hemorrhage (I61) and subarachnoid hemorrhage (I60) were defined as hemorrhagic stroke.…”
Section: Methodsmentioning
confidence: 99%
“…1, 2, 3, 4, 5, 6, 7 The Japanese Society of Hypertension Guidelines for the Management of Hypertension (JSH 2014) 8 and the European Society of Hypertension–European Society of Cardiology guidelines 9 recommend using the average of two HBP measurements obtained on one occasion to determine a person’s blood pressure. The prognostic values of the first and second HBP measurements obtained on one occasion at baseline have been investigated in the Finn-Home study 10 and the Didima study.…”
Section: Introductionmentioning
confidence: 99%